2018
DOI: 10.1111/vsu.12951
|View full text |Cite|
|
Sign up to set email alerts
|

Teaching and proficiency assessment for arthroscopy in veterinary surgery: A 2017 survey of diplomates and residents of the American and European College of Veterinary Surgeons

Abstract: Objective To determine current methods of arthroscopic skills training and proficiency assessment, identify skills considered fundamental to arthroscopy, and evaluate desire for a formal training and assessment program. Study design Anonymized electronic survey. Sample population Diplomates and residents of the American College of Veterinary Surgeons (ACVS) and European College of Veterinary Surgeons (ECVS). Methods An electronic survey was distributed in commercial software (Qualtrics, Provo, Utah). Questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…It is possible that there is some crossover between membership of different groups, and the actual number of individuals is fewer. As such, the lowest possible response rate is 6%, which is lower than a comparable minimally invasive surgery survey . Nevertheless, 149 respondents for a survey designed specifically for veterinary surgeons performing laparoscopic surgery was deemed a good response.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that there is some crossover between membership of different groups, and the actual number of individuals is fewer. As such, the lowest possible response rate is 6%, which is lower than a comparable minimally invasive surgery survey . Nevertheless, 149 respondents for a survey designed specifically for veterinary surgeons performing laparoscopic surgery was deemed a good response.…”
Section: Discussionmentioning
confidence: 98%
“…In a survey regarding arthroscopy, it was found that large animal veterinarians have more access to cadaver training than their small animal correspondents, and the lack of time, supervision, and resources were listed as the main impediments. The other categories of trainers were not used by the majority of the surgeons, with the lack of availability being primarily cited [38].…”
Section: Discussionmentioning
confidence: 99%
“…According to multiple survey studies, most veterinary surgery residency programs teach using an apprenticeshipstyle approach to learning, primarily facilitated by direct interactions between the mentor and mentee while working through requirements and a clinical case log as required by the ACVS. 21,23,24 Outside of the clinical experience and direct mentor instruction, resources and additional training are provided through textbook and journal article review, morbidity and mortality rounds, case rounds, and participation in skills practice on models and/or cadavers. 21 Private practice surgical residencies are becoming more common; presently, five of the 39 ACVS large animal residency training locations are private practices, and 54 of the 82 small animal residency training sites are private practices.…”
Section: Oversight and Approach To Resident Trainingmentioning
confidence: 99%
“…However, the completion of the required case log is the only requirement from which to infer skill acquisition during a veterinary surgical residency, and objective grading of surgical skill proficiency is rarely, if ever, performed by residency programs. 21,24 Human medical residency programs also rely on minimum case requirements to infer skill acquisition and have lamented the inherent limitations to this system, stating "there is little value in setting absolute minimum case volume requirements in the absence of direct evaluations of operative competence." 27 The ACVS residency programs do require that objective assessment of technical skills occur frequently during resident training by surgical supervisors and mentors.…”
Section: Assessment Of Competencymentioning
confidence: 99%
See 1 more Smart Citation